Hydric balance changes by cutting an adult Pinus radiata stand (Valdivia, Chile) - Huber, Anton; López, Domingo (Bosque (Valdivia), 1993)
Seasonal and spatial variations of soil-water content and water consumption by evapotranspiration were determined for and adult stand of Pinus radiata, before and after clear-cutting. These variations were compared with those of a natural prairie. Soil water reserve during winter presented changes up to 280 cm deep in the forest, while in the prairie and deforested area this only ocurred up to 100 cm. Between July 1988 and May 1989 due to evapotranspiration and interception, the forest consumed 1.031 mm of water, 80% higher than the amount consumed by the prairie (568 mm). On the other hand water consumption in the prairie surpassed the water consumed by the deforested surface in 13%. During the same period, evapotranspiration was equivalent to 96.6% and 57.7% of total precipitation for the forest and the prairie, respectively. Annual percolation for the June 1989-July 1990 period was 257 mm for the Pinus radiata stand before cutting, and 1.549 and 1.041 mm in the first and second years after cutting respectively. For the same period, percolation in the soil of the prairie was 586, 1.533 and 1.056 mm, respectively.